Financial Sector and Economic Growth in India - MacDonald, Margaux (IMF Working Papers; Working Paper, 2022)
India's financial sector has faced many challenges in recent decades, with a large, negative, and persistent credit to GDP gap since 2012. We examine how cyclical financial conditions affect GDP growth using a growth-at-risk (GaR) approach and analyze the link between bank balance sheets, credit growth, and long-term growth using bank-level panel regressions for both public and private banks. We find that on a cyclical basis, a negative shock to credit or a rise in macro vulnerability all shift the distribution of growth to the left, with lower expected growth and higher negative tail risks; over the long term, the results indicate that higher credit growth, arising from better capitalized banks with lower NPLs, is associated with higher GDP growth.